Initiation of a stable convective hydroclimatic regime in Central America circa 9000 years BP - Winter, Amos; Zanchettin, Davide; Lachniet, Matthew; Vieten, Rolf; Pausata, Francesco S. R.; Ljungqvist, Fredrik Charpentier; Cheng, Hai; Edwards, R. Lawrence; Miller, Thomas; Rubinetti, Sara; Rubino, Angelo; Taricco, Carla (Nature Communications, 2020)
Abstract Many Holocene hydroclimate records show rainfall changes that vary with local orbital insolation. However, some tropical regions display rainfall evolution that differs from gradual precessional pacing, suggesting that direct rainfall forcing effects were predominantly driven by sea-surface temperature thresholds or inter-ocean temperature gradients. Here we present a 12,000 yr continuous U/Th-dated precipitation record from a Guatemalan speleothem showing that Central American rainfall increased within a 2000 yr period from a persistently dry state to an active convective regime at 9000 yr BP and has remained strong thereafter. Our data suggest that the Holocene evolution of Central American rainfall was driven by exceeding a temperature threshold in the nearby tropical oceans. The sensitivity of this region to slow changes in radiative forcing is thus strongly mediated by internal dynamics acting on much faster time scales.